ANALYSIS OF THE IMPACT OF ATTRACTION AND GENERATION ON THE PERFORMANCE OF JALANKAPTEN A. BAKARUDIN, JAMBI CITY - Ade Nurdin; Yanuar Fitri; Nuklirullah Nuklirullah (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
One of the supports for the economy in Jambi province is the Shopping Center Development of shopping centers. Jambi Town Square Mall is one of the shopping centers in the City of Jambid with the Jambi Town Square Mall resulting in an additional volume of traffic on Jalan Kapten A. Bakarrudin No 88 Sipin Jambi City which causes a decrease in the performance of Jalan Kapten A. Bakarrudin No 88 Sipin. From the results of a field survey carried out for four days, the peak of the vehicle attraction at Jambi Town Square Mall on Monday 12 August 2020 at 19.00 WIB - 20.00 WIB was 415 vehicles / hour, Saturday 15 August 2020 at 19.00 WIB - 20.00 WIB as many as 421 vehicles / hour, Sunday, August 16 2020 at 19.00 WIB - 20.00 WIB, 596 vehicles / hour, Tuesday 375 vehicles / hour. The peak of the Jambi Town Square Mall Vehicle awakening is on Wednesday 12 August 2020 at 20.00 WIB - 21.00 WIB with a total of 411 vehicles / hour. Saturday 15 August 2020 at 20.00 WIB - 21.00 WIB with a total of 475 vehicles / hour, Sunday 16 August 2020 at 17.00 WIB - 18.00 WIB with a total of 521 vehicles / hour, Tuesday, August 18 2020 at 20.00 WIB - 21.00 WIB with a total of 469 vehicles / hour, the highest DS value is 1.028 at 17.00 WIB - 18.00 WIB